Economic and statistical analysis of industrial production in the North Caucasian Federal District of the Russian Federation - Ter-Grigoryants, Anna; Shelukhina, Elena; Leonova, Galina; Statsenko, Valeriya (Nexo Revista Científica, 2023)
The article substantiates the need to assess the industrial potential of a region to form an effective regional industrial policy with due regard to economic constraints and ongoing global exogenous changes. To attain this end, the study uses the tools and methods of mathematical statistics and system analysis. The authors of the article analyze the dynamics of industrial production in the North Caucasian Federal District of the Russian Federation, as well as the efficiency of using resources by certain industries and activities. As a result, they determine promising directions for the development of industrial potential in the region.